STUDI EKOBIOLOGI KIJING JENIS KIJING TAIWAN (Anodonta Woodiana) DI DESA SAMBORA, KABUPATEN MEMPAWAH - Fitra Wira Hadinata; Inpurwanto Inpurwanto; Sri Rahayu; Nabil Zurba (JURNAL PERIKANAN TROPIS, 2021)
Shellfish have another important role, namely the role of ecology. Therefore, a deeper knowledge of the bioecology of shellfish, especially the anatomy and environmental factors, as well as the pattern of continuous scientific studies, is required. This study aims to identify and collect information on morphometric diversity.This research will be conducted for 8 (eight) months March-October 2020 in the downstream area of Sambora Village, West Kalimantan Province. Ecological studies include observations of physical, chemical, and biological parameters as well as distribution patterns of shellfish at III observation stations. Morphometric measurements are measurements of length and weight, size class distribution, density and distribution pattern.Based on the results of research, obtained 177 individuals. The morphometric characters showed a negative allometric growth pattern of 2.10. Average density ranges from 0.37-3.02 ind/m2 with the highest average density at station I and the lowest at station III. The distribution pattern of A. woodiana at stations I and II showed the same pattern, namely random with a value of 1.00 id, while at station III the distribution pattern was uniform with a value of 0.93 id.The pH value with an average of 6, DO (Dissolved oxygen) with a range of 6.4 -7.2 mg/l,. Brightness value with a range of 22-30 cm. Depth value with an average of 40-90 cm. The average current speed value is 0.20 - 0.30 (m/s). The average percentage of sand is 85-89%, the percentage of dust is 10-11%. The abundance of plankton 80-170 individuals/l.